2010
DOI: 10.1093/jat/34.6.293
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Method for the Determination of Bisphenol A at Trace Concentrations in Human Blood and Urine and Elucidation of Factors Influencing Method Accuracy and Sensitivity

Abstract: Bisphenol A (BPA) is an industrial chemical used to make polymers including some used in food contact applications. Virtually complete presystemic clearance of orally administered BPA occurs in humans by metabolism to BPA-glucuronide (BPA-G), but some biomonitoring studies report low concentrations of free (parent) BPA in human blood and urine. Trace contamination of BPA from exogenous sources or hydrolysis of BPA-G to free BPA, either during or after biomonitoring specimen collection, may have contributed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 25 publications
2
35
0
Order By: Relevance
“…Less expensive methods have been proposed, focusing on BPA metabolites (e.g., BPA-glucuronide) [70, 71]. It has been suggested that part of the BPA measured in human samples can be due to contamination during sample collection or laboratory measurements [72, 73], and one of the great advantages of studying BPA metabolites is to avoid these contamination issues. The lower cost of these methods would also allow measuring BPA in larger populations.…”
Section: Discussionmentioning
confidence: 99%
“…Less expensive methods have been proposed, focusing on BPA metabolites (e.g., BPA-glucuronide) [70, 71]. It has been suggested that part of the BPA measured in human samples can be due to contamination during sample collection or laboratory measurements [72, 73], and one of the great advantages of studying BPA metabolites is to avoid these contamination issues. The lower cost of these methods would also allow measuring BPA in larger populations.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for assay contamination is thus not unique to BPA, and simply requires the use of standard assay procedures and appropriate controls that should be routinely employed, which has also been the conclusion reached by others (Calafat and Needham, 2009; Markham et al, 2010; Vandenberg et al, 2014a). It is important to note that the two groups of scientists that have promoted the belief that BPA cannot be assayed in human serum without contamination, the FDA laboratory (Doerge et al, 2010a; Churchwell et al, 2014), and a plastic-industry funded laboratory (Dekant and Volkel, 2008; Volkel et al, 2002), are the two laboratories that in their publications have reported uncontrolled contamination and high background BPA in their assays.…”
Section: Routes and Sources Of Bpa Exposure: Is Assay Contaminatiomentioning
confidence: 94%
“…Given this statement as a pillar for their argument that biologically active serum levels of unconjugated BPA reported in numerous studies can be ignored, along with the fact that it is contradicted by data we have presented earlier and inconsistent with standard analytic laboratory procedures, it is crucial to identify what exactly was stated in the eight studies Patterson et al (2013) cited as support for their statement (the articles cited were: Doerge et al, 2012; Koch et al, 2012; Markham et al, 2010; Salgueiro-Gonzalez et al, 2012; Teeguarden et al, 2011; Twaddle et al, 2010; Vandentorren et al, 2011; Volkel et al, 2002). In fact, examination of these publications reveals that the Patterson et al (2013) statement is not consistent with the conclusions drawn by most of the authors that they cite.…”
Section: Routes and Sources Of Bpa Exposure: Is Assay Contaminatiomentioning
confidence: 97%
See 2 more Smart Citations